Closed‐end capillary rise—An experimental study. Issue 6 (30th March 2020) - Wu, Pingkeng; Ramakrishnan, T. S.; Zhang, Hua; Wasan, Darsh T.
Abstract: The spontaneous rise of Newtonian liquids in closed‐end capillaries is investigated with three different organics. Rise rate and equilibrium height are significantly reduced by a compression induced minor elevation in air pressure within the capillaries. We verify our earlier mathematical analysis quantifying viscous dissipation within air, and also show that the dynamic contact angle plays a material role. The relative importance of these varies with capillary dimensions. We also quantify the influence of atmospheric pressure variation and the temperature induced fluctuations in the rise height. A single parameter that relates static and dynamic contact angles is sufficient to match all of the data. This parameter is obtained from an open‐capillary experiment.